Giải pt sau: \(\dfrac{\sqrt{x}-2}{\sqrt{x}-1}\) = \(\dfrac{\sqrt{x}}{\sqrt{x}+1}\)
giải hệ: \(\left\{{}\begin{matrix}\dfrac{1}{x-y}+\dfrac{1}{x+y}=2\\\dfrac{2}{x+y}+\dfrac{3}{x+y}=5\end{matrix}\right.\)
giải pt: \(\sqrt{x^2-4x+7}=\sqrt{x+1}\)
Giải PT sau
\(\sqrt{25x-25}-\dfrac{15}{2}\sqrt{\dfrac{x-1}{9}}=6+\sqrt{x-1}\)
GIẢI PT
\(\sqrt{x^2+10x+25}=4\)
\(\sqrt{x-2}+3=5\)
\(\sqrt{x^2-x+4}-x^2+x-2=0\)
\(\dfrac{\sqrt{x}-1}{\sqrt{x}+2}=\dfrac{1}{3}\)
Giải hệ PT:\(\left\{{}\begin{matrix}\dfrac{4}{\sqrt[]{2x-y}}-\dfrac{21}{x+y}=\dfrac{1}{2}\\\dfrac{3}{\sqrt{2x-y}}+\dfrac{7-x-y}{x+y}=1\end{matrix}\right.\)
rut gon pt
\(\dfrac{x+\sqrt{x}}{\sqrt{x}+1}+\dfrac{x-\sqrt{x}}{\sqrt{x}-1}\)
Tính GTLN của biểu thức A.
\(A=\dfrac{1-\sqrt{x}}{\sqrt{x}+2}\)(đk: \(x\ge0,x\ne1,x\ne4\))
B2. Giải pt
\(\sqrt{x-3}+\sqrt{y-5}+\sqrt{z-4}=20-\dfrac{4}{\sqrt{x-3}}-\dfrac{9}{\sqrt{y-5}}-\dfrac{25}{\sqrt{z-4}}\)
giải pt \(\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}\ge\dfrac{3}{2}\)
\(\dfrac{\sqrt{x-1}}{\sqrt{x}+1}=2\)
giải pt